Seasonal Methane and Nitrous Oxide Emissions of Several Rice Cultivars in Direct‐Seeded Systems. Issue 1 (1st January 2015) - Simmonds, Maegen B.; Anders, Merle; Adviento‐Borbe, Maria Arlene; van Kessel, Chris; McClung, Anna; Linquist, Bruce A.
Abstract : An understanding of cultivar effects on field greenhouse gas (GHG) emissions in rice ( Oryza sativa L.) systems is needed to improve the accuracy of predictive models used for estimating GHG emissions and to evaluate the GHG mitigation potential of different cultivars. We compared CH4 and N2 O emissions, global warming potential (GWP = N2 O + CH4 ), yield‐scaled GWP (GWPY = GWP Mg −1 grain), and plant growth characteristics of eight cultivars within four study sites in California and Arkansas. Nitrous oxide emissions were negligible (<10% of GWP) and were not different among cultivars. Seasonal CH4 emissions differed between cultivars by a factor of 2.1 and 1.4 at one California and one Arkansas site, respectively. Plant growth characteristics were generally not correlated with seasonal CH4 emissions; however, the strongest correlations were observed for shoot and total plant (root + shoot) biomass at heading ( r = 0.60) at one California site and for grain at maturity ( r = −0.95) at one Arkansas site. Although differences in GWP and GWPY were observed, there were inconsistencies across sites, indicating the importance of the genotype × environment interaction. Overall, the cultivars with the lowest CH4 emissions, GWP, and GWPY at the California and Arkansas sites were the lowest and highest yielding, respectively. These findings highlight the potential for breeding high‐yielding cultivars with low GWP, the ideal scenario to achieve low GWPY, but environmental conditions must also be considered.